(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
Learning in elementary school students can be done through several learning methods to intervene in learning outcomes. Guided discovery learning can be one of the learning models that can be applied, because of the evidence from several existing studies. The purpose of this study was to analyze the intervention of guided discovery learning on learning outcomes in elementary school students. This type of research is descriptive qualitative with literature review method. 13 journals have been selected from 30 journals that have been collected based on established criteria. The review process uses a synthesis matrix in the form of a table with columns of reference sources, samples, methods, instruments, and research results. The results of the review show that 62% of previous studies used classroom action research methods and 38% used experimental methods. The sample of the previous research consisted of 4% of class 3, and 46% of class 4 and 5, while the 100% learning outcome measurement instrument was obtained from observation sheets or questions related to the material described. The results of the research from the review process of previous studies show that guided discovery learning helps students understand the material thoroughly through learning stages that are easy to follow by students, so that students are able to apply it to find a solution to the problems that occur. Based on these results, it is necessary to have a variety of learning methods, one of which is using guided discovery on difficult learning materials.